Do Marketing strategies, COVID 19 Pandemic and Consumer Location Affect Consumer Buying Behaviour? Empirical Study on Oil and Gas Lubricant Industries in United Arab Emirates - Hosam Azat Elsaman; Liza Gernal (Philippine Association of Institutions for Research, Inc., 2021)
For UAE end-users, consumer behavior and purchasing power faced many swings period after Covid 19 pandemic. Recently, changes in sales capacity and customers' preferences for eco-friendly products highlighted the industrial gap for producers before and after the pandemic. Green marketing practices aim to improve customer knowledge to increase consumer loyalty, preserve wealth, and reduce global environmental degradation. The research examines the relationship between changes in consumer purchasing behavior and green marketing strategies following the COVID-19 pandemic in the UAE's oil and gas lubricants industry. It also assesses the efficacy of green marketing in improving the dynamic of organization performance. Stakeholders and three bottom lines theories formed the theoretical background for this research. The paper's methodology is quantitative with deductive approaches and inferential statistical analysis, while the sampling strategy is a snowball, with 162 respondents, through quantitative methods, most notably surveys. The primary findings of this study established a substantial positive correlation between both study variables and consumer attitudes toward green marketing initiatives. Consumer opinion differs according to geographical ages when developing and advertising environmentally friendly products. Meanwhile, the article examined how consumers' behavior of economic themes changed prior to and following the Covid-19 pandemic epidemic.